2023
DOI: 10.1017/s1478951523000378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of chronic nonmalignant pain in palliative care populations: A systematic review

Abstract: Objectives To investigate the prevalence and current approaches to clinical management of chronic nonmalignant pain in patients referred to palliative care services. Methods A systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and registered with PROSPERO (CRD42021205432). Six databases were searched on 25 August 2020 and again on 11 July 2022: PubMed and Ovid MEDLINE, Elsevier Scopus, PsychINFO, the Cochrane Library, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus, the palliative care population is quite diverse, as it contains individuals of a broad age range with a wide variety of diseases, complications, and comorbidities. A systematic review found that the estimated prevalence of chronic, nonmalignant pain among patients receiving various types of palliative care ranged from 14% to 34% [8], and in one study, ~22% of individuals receiving palliative home care reported severe daily pain in their last month of life [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the palliative care population is quite diverse, as it contains individuals of a broad age range with a wide variety of diseases, complications, and comorbidities. A systematic review found that the estimated prevalence of chronic, nonmalignant pain among patients receiving various types of palliative care ranged from 14% to 34% [8], and in one study, ~22% of individuals receiving palliative home care reported severe daily pain in their last month of life [9].…”
Section: Introductionmentioning
confidence: 99%